Intercultural Communicative Competence: Why Is It Significant and How Can It Be Enhanced in EFL Settings? - Seçil Tümen Akyıldız; Vildan Çelik; Kwestan Hussein Ahmed (Yaşadıkça Eğitim, 2021)
In the current literature on foreign language teaching, it has become clear that having the requisite ability of intercultural communicative competence (ICC) to be aware of different cultures, respect them, and interact with people from different cultures is crucial. Language is connected to culture and societies, in which people need to communicate with one another. English as a lingua franca provides a means of communication among different cultures. Thus, English as a foreign language (EFL) teaching classes offer perfect situations to foster ICC. From this viewpoint, this article gives an account to raise awareness of ICC in EFL settings by explaining ICC and its relationship with language, describing the significance of ICC, and illustrating some suggestions in the literature for the enhancement of ICC in EFL classes. This paper seeks to improve EFL teachers’ understanding of intercultural communication and to help them with their classroom practices.